A Study on the Impact of Natural Disasters on Farmers’ Relative Poverty - Li, XiJian; Zheng, JiaXi; Lu, Honggang (Frontiers in Environmental Science, 2022)
In 2020, China announced the successful completion of its poverty alleviation mission, noting that the focus of China’s poverty alleviation mission has shifted from eliminating absolute poverty to alleviating relative poverty. Due to global warming and frequent natural disasters, natural disaster shocks have seriously affected farmers’ livelihoods and aggravated relative poverty. Based on 5,804 rural household samples from the China Family Panel Studies, the impact of natural disasters on farmers’ relative poverty was investigated using the logit model. In addition, the interaction terms between the impact and intensity of natural disasters, non-agricultural employment and productive investment were included in the model. The results show that: (1) Natural disaster shocks and natural disaster intensities had a significant positive impact on farmers’ relative poverty. (2) Migrating for work and stable employment effectively alleviated the positive impact of natural disaster shocks and natural disaster intensities on farmers’ relative poverty, respectively. (3) Productive investment weakened the positive impact of natural disaster shocks on farmers’ relative poverty. (4) Scale management effectively alleviated the positive impact of natural disaster shocks on farmers’ relative poverty, but the moderating effect of scale management was not significant in areas with high disaster intensities.